An Evaluation Study of the Classroom Activities within the Developed English Course (Flying High) for the High School First- Grade Students in View of Creative Thinking Skills (Journal Of Educational and Psychological Researches, 2023)
The study aims to examine the classroom activities of the developed English course (Flying High) for the high school first-grade students, identify creative thinking skills appropriate for this grade, and show the extent the classroom activities involve these skills from the female- teachers ‘point of view. The study adopted the descriptive survey method. The study community consists of all (50) English female-teachers who teach high school first grade in Arar city during the academic year (1440 -1441 A.H, the first semester). The study was applied to all respondents. The researcher used a questionnaire as a study tool. The study revealed that the female-teachers reported their disagreement and refusal of the classroom activities in the developed English language course (Flying High) for high school first-grade students, by 2.50 of 4.00 (arithmetic mean ). The most important features for this are the accumulation of classroom activities in one lesson, and no consideration of the individual differences between female students. It also found that English female-teachers do not agree with the availability of creative thinking skills in the classroom activities in the developed English course for those students. Among these skills, the most important one is the possibility of providing various responses while brainstorming a proper number of ideas at a specific time, regardless of the level and type of the idea. The study presented a number of recommendations: the classroom activities of the English course (Flying High) are to be linked to female- students’ needs in their daily life; the activities have to include attractive and interesting elements, in order to increase female- students' motivation towards practicing these activities and using them in their lives.